2021
DOI: 10.3390/ma14113079
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Cement Substitution by Biomass Fly Ash on the Polymer–Cement Composites Properties

Abstract: The generation of energy for the needs of the population is currently a problem. In consideration of that, the biomass combustion process has started to be implemented as a new source of energy. The dynamic increase in the use of biomass for energy generation also resulted in the formation of waste in the form of fly ash. This paper presents an efficient way to manage this troublesome material in the polymer–cement composites (PCC), which have investigated to a lesser extent. The research outlined in this arti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 24 publications
0
8
0
Order By: Relevance
“…They also have the most ash, which is another reason to use parsley root peels as co-feed in order to reduce the amount of ash slag from such a power plant. Considering the fact that the willow exhibits a much different ash composition, with calcium carbonate being the main constituent rather than a potassium-containing compound, it could be added as co-feed to control the ash/slag composition for the application of such ash/slag in, e.g., cement production [ 48 , 49 ].…”
Section: Resultsmentioning
confidence: 99%
“…They also have the most ash, which is another reason to use parsley root peels as co-feed in order to reduce the amount of ash slag from such a power plant. Considering the fact that the willow exhibits a much different ash composition, with calcium carbonate being the main constituent rather than a potassium-containing compound, it could be added as co-feed to control the ash/slag composition for the application of such ash/slag in, e.g., cement production [ 48 , 49 ].…”
Section: Resultsmentioning
confidence: 99%
“…Biomass fly ash that derives from the combustion of herbaceous energy crops tends to have a higher percentage of alkaline oxides in its chemical oxide composition than coal fly ash, whereas woody biomass fly ash tends to have a higher content of calcium oxide (up to 80%). Even so, SiO 2 content can be as high as 68%, and the overall chemical oxide composition of this type of fly ash can be similar to that of Class C fly ash [17][18][19][20]. Mixed reports have been published on the mineralogical composition and content of reactive phases in biomass fly ashes [21][22][23][24].…”
Section: Introductionmentioning
confidence: 98%
“…In comparison with coal fly ash, the limited number of harmful elements in BFA also significantly reduces the adverse effects on human health and the natural environment [ 8 , 13 ]. Jaworska et al [ 14 ] confirmed the feasibility of agricultural BFA as a mineral admixture in polymer-modified cement composites by examining its gradation and activity index and also revealed that the addition of BFA significantly enhances compressive strength. Thiedeitz et al [ 7 ] used rice husk ash as SCM and investigated its contribution to mortar microstructure, strength, and durability properties; the enhanced strength development along with low water absorption and small capillary porosity indicated that rice husk ash is a suitable pozzolanic admixture.…”
Section: Introductionmentioning
confidence: 99%
“…Thiedeitz et al [ 7 ] used rice husk ash as SCM and investigated its contribution to mortar microstructure, strength, and durability properties; the enhanced strength development along with low water absorption and small capillary porosity indicated that rice husk ash is a suitable pozzolanic admixture. The reactivity of BFA is lower than OPC, and the mixture containing BFA usually increases the amount of water needed for maintaining the desired rheology of the fresh mixture [ 14 ]. It is known that the workability and mechanical strength of mixtures containing BFA depend on the dosage of BFA [ 14 , 15 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation